Experimental and Molecular Docking Study of 3′,4′,5′-Trimethoxychalcones Targeting Overexpressed Protein in HCT-116 Colon Cancer Cells - Danova, Ade; Wonganan, Piyanuch; Hermawati, Elvira; Kurniadewi, Fera; Musthapa, Iqbal; Chavasiri, Warinthorn (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
Cancer poses a substantial global health challenge. Colorectal cancer (CRC) is the second leading cause of cancer-related mortality after lung cancer and is associated with high mortality rates worldwide. Chalcones have attracted significant interest because of their diverse biological properties, including potential anticancer effects. In this study, five 3′,4′,5′-trimethoxychalcones (1-5) were tested against HCT-116 colon cancer cells using an MTT assay for the first time. Molecular docking was conducted to predict molecular interactions targeting three proteins (tubulin, EGFR, and CDK2). Among the five, four compounds (1, 3, 4, and 5) exhibited strong inhibitory activity against HCT-116 colon cells, with IC50 values < 10 µM. Compounds 1-5 showed potency as drug candidates based on the Lipinski rules and pharmacokinetic profiles using SwissADME and pkCSM online tools. Moreover, molecular docking was performed on compound 5 against three protein targets (tubulin, EGFR, CDK2) with binding affinities of -7.4, -7.3, and -8.5 kcal/mol, respectively, and showed major H-bond interactions. Therefore, these results suggest that compound 5 could be a potential inhibitor to be developed in future studies, both in vitro and in vivo, to understand its inhibition mechanism and efficacy.